THU0101 Real-World Evaluation of TNF Inhibitor Utilisation in Patients with Rheumatoid Arthritis in a us Claims Database. (9th June 2015) - Harnett, J.; Wiederkehr, D.; Gerber, R.; Gruben, D.; Koenig, A.; Bourret, J.
Abstract : Background: Tumour necrosis factor inhibitors (TNFi) have transformed the management of rheumatoid arthritis (RA). However, 28–41% of patients (pts) with RA receiving TNFi in clinical trials do not achieve an ACR20 response; 1 inferior outcomes are usually observed when used without conventional synthetic DMARDs (csDMARDs). 2 Objectives: To evaluate 12-month (mo) treatment patterns, healthcare resource use (HCRU) and costs for pts with RA after initiation of index TNFi and switch from index TNFi to second-line biologic agent. Methods: This was a retrospective cohort analysis of pts aged ≥18 years with ≥2 outpatient or 1 inpatient visits for RA (ICD-9 code: 714.xx) who initiated TNFi in a US claims database (Truven Marketscan® Commercial Claims and Encounters and Medicare Supplemental Databases; 2010–2013). Pts with another inflammatory disease diagnosis of interest or who had pre-index biologic agent or >1 biologic agent within 14 days (d) were excluded. Treatment patterns were characterised by start of non-index biologic agent (switchers), gap >180 d between index prescription/administration and no other biologic agent (discontinuers) or no gap >180 d and no other biologic agent (continuers). Treatment patterns and all-cause/RA-related HCRU and costs were assessed over 12 mos post-index and in a subset of switchers within 180 d of last index TNFi prescription/administration who had another 12 mos continuous enrolment post-switch. Results: 9567 pts initiated TNFi, 44.6% without csDMARD. During follow-up (FU), 67.2% of pts were continuers, 17.3% discontinuers and 15.4% switchers (Figure ). Switchers had greatest unadjusted 12-mo mean all-cause total costs (34585) vs continuers (33051) and discontinuers (24915); 85.7%, 82.8% and 31.4%, respectively, of total costs were RA-related. Most of the 12-mo mean RA-related total cost (24319) for all pts was due to prescriptions (74.4%) and outpatient visits (23.6%). Of 764 switchers with 12 mos continuous enrolment post-switch, 68.2% switched to alternative TNFi and 31.8% to non-TNFi biologic agent. Overall, 36.7% of pts who switched from index TNFi to second-line TNFi switched again during 12 mos of FU vs 27.6% of pts who switched from index TNFi to non-TNFi biologic agent (p=0.0134; Figure ). Pts who switched to non-TNFi biologic agent had greater unadjusted 12-mo mean all-cause total costs (76580) vs those who switched to an alternative TNFi (50689). RA-related costs accounted for 58.4% and 54.3% of total costs for pts who switched to non-TNFi biologic agent and alternative TNFi, respectively. Biologic administration visits accounted for 78.8% (14205) of the greater total RA-related costs of pts who switched to non-TNFi biologic agent vs alternative TNFi. Conclusions: In a US claims database, a large proportion of pts initiated TNFi without csDMARD. Real-world TNFi discontinuation/switch rates were similar to previous non-response rates. 1 Pts who switched from TNFi to non-TNFi biologic agents were less likely to switch again but had greater costs overall, mostly due to biologic administration visits. References: Agarwal SK et al. J Rheumatol 2008; 35: 1737-1744. Emery P et al. Ann Rheum Dis 2013; 72: 1897-1904. Acknowledgements: This study was sponsored by Pfizer Inc. Editorial support was provided by Karen Irving at Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: J. Harnett Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., D. Wiederkehr Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., R. Gerber Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., D. Gruben Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., A. Koenig Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Bourret Shareholder of: Pfizer Inc., Employee of: Pfizer Inc.